2022
DOI: 10.3389/fpls.2022.1021483
|View full text |Cite
|
Sign up to set email alerts
|

Sprayed biodegradable liquid film improved the freezing tolerance of cv. Cabernet Sauvignon by up-regulating soluble protein and carbohydrate levels and alleviating oxidative damage

Abstract: Most cultivars of Vitis vinifera L. are very sensitive to cold. As an exogenous protectant, Biodegradable Liquid Film (BLF) is considered to protect winegrapes from low temperatures and dry winds for safe overwintering. This study aimed to reveal the physiological and biochemical mechanisms of BLF regulating the freezing tolerance of wine grapes. Groups of ten-year-old vines (Cabernet Sauvignon) were sprayed with BLF in November 2020 and 2021, or left untreated as a control treatment, and field plant mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The electrolyte leakage of dormant cuttings branches was first measured in this study ( Figure 1 A), and two temperatures with relative conductivities close to 50% (−10 °C) and 80% (−16 °C) were selected for the next analysis. Based on our previous study [ 35 ], three time points of 3, 6, and 12 h of low-temperature stress were identified as sampling points. The malondialdehyde (MDA) content of branches at three time points was measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrolyte leakage of dormant cuttings branches was first measured in this study ( Figure 1 A), and two temperatures with relative conductivities close to 50% (−10 °C) and 80% (−16 °C) were selected for the next analysis. Based on our previous study [ 35 ], three time points of 3, 6, and 12 h of low-temperature stress were identified as sampling points. The malondialdehyde (MDA) content of branches at three time points was measured.…”
Section: Resultsmentioning
confidence: 99%
“…After natural dormancy in December, the vines in the pots were transferred to the high- and low-temperature alternating test chamber (YSGJS-408, Shanghai Lanhao Instrument & Equipment Co., Ltd., Shanghai, China) for freezing stress treatment. The low-temperature treatment referred to the method of Han et al [ 35 ], and the rate of cooling and rewarming was 4 °C/h. The branch samples for electrolyte leakage measured were treated at −6 °C, −8 °C, −10 °C, −12 °C, −14 °C, −16 °C, −18 °C, and −24 °C for 12 h and recovered at 4 °C for 12 h. The samples for transcriptomic analysis were treated at −10 °C and −16 °C for 3 h, 6 h, and 12 h, frozen in liquid nitrogen immediately and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can neutralize reactive oxygen species generated by oxidative stress and adjust the intracellular redox balance [69], as well as reduce oxidative damage to cell membranes and intracellular organelle structures. Together, they maintain the stable growth and survival of woody plants under high-temperature conditions [70]. This shows that woody plants can improve the activity of antioxidant enzymes, reduce the oxidation of cells and maintain structural stability under high-temperature stress.…”
Section: Effect Of Antioxidase Activitymentioning
confidence: 89%
“…Research has shown that high-chilling-tolerance cultivars accumulated more antioxidants, enzymes and osmoregulation substances in the anti-stress and environment adaption process compared with low-chilling-tolerance cultivars [41,42]. In more detail, the functions of the soluble protein and carbohydrate levels on the improvement in freezing tolerance were validated in sauvignon [43], while the functions of increased proline and carbohydrates under cold stress were also verified in alfalfa [44]. Furthermore, the enhanced chilling tolerance in watermelon achieved via suboptimal temperature acclimation was contributed to by improved photosynthetic adaptability and osmoregulation ability from substances such as proline, soluble sugar and sucrose [45].…”
Section: Antioxidase and Osmoregulation Substances Played Important R...mentioning
confidence: 99%